PENGELOLAAN FASILITAS DI OBJEK WISATA ASIA FARM KOTA PEKANBARU - Harahap, Ardhini Fadhlika; ', Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Tourism plays an important role in regional economic development, with facilities as a major component in supporting visitor comfort and satisfaction. Asia Farm, located in Pekanbaru City, is a rapidly developing tourist attraction that offers educational and recreational experiences. This study aims to examine the management of facilities at Asia Farm Pekanbaru and identify the obstacles faced during operation. This study uses a descriptive qualitative approach, with data collection through observation, interviews, and documentation. Key informants include managers responsible for supervising facilities, working staff, and several tourists. The results of the study show that Asia Farm implements facility management through structured stages, namely: planning, organizing, implementing, and controlling. Staff assignments and task monitoring are carried out through digital applications to ensure real-time reporting. Although most of the facilities are well maintained, there are still problems such as damaged infrastructure and limited supporting facilities such as parking areas. In conclusion, the management of Asia Farm facilities is well organized but needs to be further improved in supervision and maintenance to improve service quality and increase visitor satisfaction and comfort. Keywords : Facilities, Management, Tourism, Asia Farm.